The evolution of floral ontogenetic allometry in the Andean genus Caiophora (Loasaceae, subfam. Loasoideae). Issue 1 (15th December 2017) - Strelin, Marina Micaela; Benitez‐Vieyra, Santiago; Fornoni, Juan; Klingenberg, Christian Peter; Cocucci, Andrea
Abstract : The astounding variety of angiosperm flower morphologies has evolved in response to many selective forces. Flower development is highly coordinated and involves developmental associations between size and shape, ontogenetic allometry, which in turn affect the morphology of mature flowers. Although ontogenetic allometries can act as a developmental constraint and may influence adaptive evolution, allometries can evolve themselves and may change rapidly in response to selection. We explored the evolution of ontogenetic allometry in the flowers of 11 species of Loasoideae. Seven species belong to Caiophora, which radiated recently in the central Andes, and contains species that are pollinated by bees, hummingbirds, and small rodents. According to a previous study, the diversification of Caiophora involved departures from simple allometric scaling, but the changes to allometry that enabled flower diversification have not been explored yet. We characterized the ontogenetic allometry of each species with the methods of geometric morphometrics. We studied the evolution of allometries by constructing allometric spaces, in which the allometry of each species is represented by a point and the arrangement of points indicates the relations among allometric trajectories. To examine the history of changes of ontogenetic allometries, we projected the phylogeny into the allometric spaces. Inspection of allometric spaces suggests that ontogenetic variation is limited to a few dominant features. The allometries of the two main functional flower parts under study differ in their evolutionary labilities, and patterns of variation reflect pollination systems, differences in structural organization, and abiotic environmental factors.